A Study on Cadaveric Dry Skulls to Calculate the Incidence of types of Pterion in North-West Indians - Sharma, Suresh; Parashar, Rekha; Gupta, Upendra Kumar; Verma, Pooja Kumari (International Journal of Scientific Research in Biological Sciences, 2020)
Pterion is a small area present in the temporal fossa and is covered by temporal muscle and temporalis fascia. Pterion is formed on norma laterals where 4 bones greater wing of sphenoid, parietal, frontal, and squamous part of the temporal bone articulate with each other. The aim of present study is to calculate the incidence of different shapes of the pterion. This study was conducted on 108 human dry skulls in the Department of Anatomy, National Institute of Medical Sciences and Research, Jaipur. The following parameters Sphenoparietal, Frontotemporal, Epipteric and Stellate were observed in pterion and noted down in table format. The study was conducted on 108 human dry skulls and 216 types of pterion were observed where 133 sphenoparietal, 60 were frontotemporal type, 23 were epipteric type and no incidence of stellate type. Sphenoparietal type of pterion was the most dominant type of pterion which was observed in 61.57%of cases. This study will be helpful to anatomists, neurosurgeons, anthropologists and researchers. This study concludes that the knowledge of the position of pterion will be helpful for burr hole surgeries and neurosurgeries, anatomists, anthropologists and researchers.